Clinical and microbiological features of bacteraemia with Gram-positive anaerobic cocci: a population-based retrospective study. (June 2019) - Badri, M.; Nilson, B.; Ragnarsson, S.; Senneby, E.; Rasmussen, M.
Abstract: Objectives: Gram-positive, anaerobic cocci (GPAC) can cause infections in humans. Only a few cases of bacteraemia with GPAC have been reported. We describe the clinical and microbiological characteristics of GPAC bacteraemia. Methods: A retrospective population-based study of GPAC bacteraemia 2012–2016 in southern Sweden was performed. GPAC were identified using matrix-associated laser desorption ionization time-of-flight mass spectrometry or 16S rRNA gene sequencing. Etests were used to determine antibiotic susceptibilities. Data on patient and infection characteristics, treatment, and outcome were collected from the medical records. Results: A total of 226 episodes of GPAC bacteraemia in adults were studied; this corresponds to an annual incidence of 3.4 cases per 100, 000 persons per year. The bacteria identified were Anaerococcus spp. ( n  = 43), Atopobium spp. ( n  = 7), Blautia spp. ( n  = 1), Finegoldia spp. ( n  = 15), Parvimonas spp. ( n  = 100), Peptoniphilus spp. ( n  = 52), Peptostreptococcus spp. ( n  = 2), and Ruminococcus spp. ( n  = 9) of which 200 isolates were identified to the species level. Resistance to imipenem and piperacillin was not identified, whereas resistance among the 229 isolates to penicillin was detected in four, to metronidazole in six, and clindamycin in 16 isolates. The median age of patients was 73 years (55–83, IQR), 57% were male and comorbidities were common. Fifty-one per cent of infections were polymicrobial. In 60% of cases a focus of infection was identified. Forty per cent of patients had either organ dysfunction or shock. The 30-day mortality was 11%, and nosocomial infections were over-represented among the deceased. Conclusions: GPAC bacteraemia is much more common than previously reported. GPAC-bacteraemia is a condition with significant mortality mainly affecting elderly persons with comorbidities.